PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SUMBER ALFARIA TRIJAYA, TBK AREA CILEUNGSI - Peby Phillip Butar Butar; Nuridin (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
Purpose to determine the effect of compensation and work discipline on employee work productivity PT. Sumber Alfaria Trijaya, Tbk Area Cileungsi. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to 62 respondents, all of whom were employees of PT. Sumber Alfaria Trijaya, Tbk Area Cileungsi. The research method using partially and simultaneous linear regression analysis. The results of the study indicate that simultaneous or partially, compensation and work discipline have a positive and significant effect on employee work productivity.